Spine–Hip BMD Discordance and Age-Dependent Divergence Between T-Scores and Z-Scores at DXA: A Cross-Sectional Study - Tabassum, Ilteza; Jabin, Zeenat; Naznin, Afroza; Sultana, Jerin (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Spine–hip bone mineral density (BMD) discordance complicates dual-energy X-ray absorptiometry (DXA) interpretation and may affect osteoporosis classification. This study assessed the prevalence of spine–hip discordance and the age-dependent divergence between T-scores and Z-scores. Methods: This cross-sectional study included 292 apparently healthy individuals who underwent DXA. BMD, T-scores, and Z-scores were analyzed at the lumbar spine, left femur, and right femur. Spine–hip discordance was defined as an absolute difference of at least 1.0 SD between the lumbar spine T-score and either femoral T-score and was categorized as minor (1.0 to <2.0 SD) or major (≥2.0 SD). The T–Z gap was defined as T-score minus Z-score. Inter-site differences were assessed using repeated-measures ANOVA, and associations between age and T–Z gap were evaluated using Pearson correlation. Results: Participants were predominantly female (84.9%). The lumbar spine showed the lowest score profile, with mean T-scores of −1.36 ± 1.64 at the lumbar spine, −0.08 ± 1.16 at the left femur, and −0.17 ± 1.27 at the right femur. Corresponding mean Z-scores were −0.19 ± 1.62, 0.57 ± 1.10, and 0.48 ± 1.20, respectively (all inter-site comparisons, p < 0.001). Overall, 73.3% of subjects demonstrated spine–hip discordance, including 41.1% with minor and 32.2% with major discordance. Age was strongly negatively correlated with the T–Z gap at all sites (r = −0.892, −0.886, and −0.888; all p < 0.001). Osteoporosis prevalence increased from 3.1% by hip-only classification to 29.1% by worst-site classification. Conclusion: Spine–hip discordance is highly prevalent, predominantly spine-driven, and associated with substantial age-related T/Z divergence and diagnostic reclassification. Bangladesh J. Nuclear Med. 28(2): 314-320, July 2025